Gender politics and activism: a comparative study of African National Congress Youth League branches in Seshego (Limpopo) - Mafatshe, Itumeleng (My University, 2016)
The question of gender inequality in South Africa has still not received the platform that it deserves. This reality may be attributed to numerous factors including the masculine attitudes that continue to prevail in South African politics. This dissertation therefore analyses the construction of gender roles in youth political organisations in South Africa, and investigates how hegemonic gender formations challenge and shape the activism of women within these organisations. It focuses on the largest and oldest youth political formation in the country, the African National Congress Youth League (ANCYL). It draws from the rich history of the ANC and the Mass Democratic Movement (MDM) to understand better the framework of current gender politics. Feminist theory is used as the underpinning theoretical framework throughout this research, thus providing a new perspective of women’s activism that goes beyond the traditional practices employed in research about political organisations. This dissertation is informed by a qualitative research approach with a focus on interviews with individuals who are members of the ANCYL in the Seshego township in South Africa’s Limpopo Province. The main argument made in this dissertation is that women in mainstream political organisations like the ANCYL continue to experience difficulties in the assertion of their activism because of the historically dominating masculine characteristics of such organisations. A nuanced analysis of young women’s activism in South Africa is the major contribution that this research offers. By bringing forth the narrative of ordinary female activists, this dissertation deliberately confronts the celebration of the supposedly already realised gender equality, arguing that this is a premature celebration that is not cognisant of the daily experiences of female activists of the ANCYL.
A thesis submitted in fulfilment of the requirements for the degree of Master of Arts University of the Witwatersrand Department of Political Studies February 2015
Keywords: African National Congress. Youth League; Gender identity--Political aspects; Sex role--Political aspects--South Africa; Youth--Political activity--South Africa